Jointing composition and chemical composition of Creole goats as influenced by body condition - AUMONT, G; CALIF, B; FEUILLET, D; MARIVAL, P; ALEXANDRE, G (The Indian Journal of Animal Sciences, 2013)
The purpose of this study was to determine the effects of body condition estimated by a body composition score of 5 levels (BCS) on slaughter traits, tissue composition of empty body weight (EBW), and joining and chemical composition of carcass in Creole does. During 3 months, 3 groups of 6 Creole female goats were fed 3 different diets composed of Panicum maximum and concentrate, to induce different body compositions. Mcans of BCS were 1.8, 2.4, 3.1 for grOups 1, 2. and 3 respectively. The body composition was assessed after slaughter, by the weight of different fat tissues in EBW, skin appendages and dressed carcass, and by the dissccLion and chemical analysis of the left shoulder freezed for 24 hr at 4 oC. The EBW ranged from 16.9 to 21.4 kg. The adipose tissues of the carcaSses estimated from the dissection of the shoulder varied from 1.3 to 11.5% of shoulder. The total adipose tissues in EBW ranged from 7.1 10 15.2% EBW. Chemical composition of muscle and adipose tissue was greatly affected by body condition. The mass losses in EBW. The mass losses in EBW mass (4.5 kg for group 3 YS group 1; 1.7 kg for group 3 vs group 2) were composed by the abdominal adipose tissue for34 to 50%, and 51 to 48% by the carcass, respectively, for groups 1 and 2.